PLAYING IN EARLY CHILDHOOD EDUCATION - da Silva, Elitânia; Amaral Ramos, Clemilde; Antônia da Silva Mendes, Maria; Trevizan Tramontina, Franciele; Maria da Silva, Jessica (Revista Gênero e Interdisciplinaridade, 2024)
Play is an essential form of communication and learning for children, allowing them to reproduce their daily lives, develop reflection, autonomy and creativity. Through play, children face fears and insecurities, interact socially and build knowledge in a playful way. This study highlights the importance of playing in child development, showing that playful activities are fundamental to both mental and body development. In addition, play helps in socialization, respect for rules and development of imagination. Early childhood education should incorporate the playful as an integral part of the teaching process, promoting significant and pleasurable learning.